Koasekuracja w świetle przepisów europejskiego prawa antymonopolowego - Orlicka, Justyna (Coinsurance in the Light of European Competition Rules, 2008)
Since the judgement of the Court of Justice Verband der Sachversicherer (Case 45/85) of 27.01.1987, there is no longer any doubt, that European competition rules are fully applicable to the insurance sector. The prohibition of anti-competitive agreements between undertakings, incorporated in Article 81 (1) of the Treaty, refers also to coinsurance contracts. However, because of the fact that co-operation between insurance undertakings is, to a certain extent, desirable to ensure the proper functioning of this sector and may at the same time promote consumer's interests, coinsurance contracts are, under specified circumstances, exempted from the prohibition from Article 81 (1) of the Treaty. The author describes rules governing this exemption, basing on Commission Regulation (EC) No 358/2003 of 27.02.2003 on the application of Article 81 (3) of the Treaty to certain categories of agreements, decisions and concerted practices in the insurance sector. Moreover, the author considers the concept of coinsurance, trying to find a solution useful both for competition and for civil law.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 294-301